Resiliensi Siswa: Bagaimana Peran Orang Tua Membentuk Ketahanan Anak - Althaf, Tsabitah; Nur, Kur'ani; Riszky, Ramadhan (Psikodidaktika, 2024)
This research aims to examine the significant influence of parental roles on students' resilience. The research method used in this study is a quantitative research method. The population in this study is all students of MAN 2 Pontianak City. Therefore, the sampling technique in this study is cluster random sampling. The sample size in this study is 30 respondents. The analysis method in this study is simple linear regression analysis. The measurement tools in this study use a resilience scale and a parental role scale. The reliability test used the alpha technique with Cronbach's Alpha Guilford > 0.80. The normality test used the Kolmogorov-Smirnov test with a result of 0.200, while the linearity test used the ANOVA tabel with a significance value of deviation from linearity of 0.325 > 0.05. The result of the simple linear regression test in this study was 0.017 < 0.05, which means the research hypothesis is accepted, indicating that there is an influence of parental role on students' resilience. The result of the determination test with an R Square of 0.186 indicates that the influence of the parental role variable on the resilience variable is 18.6%.